Mastering SoapUI : master the art of testing and automating your SOA using SoapUI - Nandan, Pranai (Packt Publishing, 2016)
Master the art of testing and automating your SOA using SoapUI About This Book Design real-time test automation frameworks for Enterprise applications using SoapUI Learn how to solve test automation issues for complex systems A complete guide to understanding SOA automation from quality assurance to business assurance Who This Book Is For The book is intended for test architects, SOA test specialists, automation testers, test managers, and software developers who have a good understanding of SOA, web services, Groovy Scripting, and the SOAP UI tool. What You Will Learn Familiarize yourself with Test Web services from functional, nonfunctional, and security aspects Learn to test real-time service orchestrations Design test automation solutions for SOA-based Enterprise applications Learn multilayer test automation Selenium plus SoapUI under a single umbrella Integrate your SoapUI framework with Jenkins In Detail SoapUI is an open-source cross-platform testing application that provides complete test coverage and supports all the standard protocols and technologies. This book includes real-time examples of implementing SoapUI to achieve quality and business assurance. Starting with the features and functionalities of SoapUI, the book will then focus on functional testing, load testing, and security testing of web services. Furthermore, you will learn how to automate your services and then design data-driven, keyword-driven, and hybrid-driven frameworks in SoapUI. Then the book will show you how to test UIs and services using SoapUI with the help of Selenium. You will also learn how to integrate SoapUI with Jenkins for CI and SoapUI test with QC with backward- and forward-compatibility. The final part of the book will show you how to virtualize a service response in SoapUI using Service Mocking. You will finish the journey by discovering the best practices for SoapUI test automation and preparing yourself for the online certification of SoapUI. Style and approach Filled with real-time examples, this book will help readers take their knowledge to the next level. This book is a comprehensive guide that will cover the end-to-end life cycle of implementing SoapUI in various phases of software testing and the software development life cycle.
Includes index.
Keywords: Service-oriented architecture (Computer science) -- Testing.; elektronické knihy; electronic books